ChemInform Abstract: Utilization of LDH‐Based Materials as Potential Adsorbents and Photocatalysts for the Decontamination of Dyes Wastewater: A Review. Issue 43 (7th October 2016) - Yang, Zhongzhu; Wang, Fenghua; Zhang, Chang; Zeng, Guangming; Tan, Xiaofei; Yu, Zhigang; Zhong, Yu; Wang, Hou; Cui, Fang
Abstract: Review: 166 refs.